Comparison of Intravitreal Anti-VEGF Agents With Laser Photocoagulation for Retinopathy of Prematurity of 1,627 Eyes in China - Linghu, Dandan; Cheng, Yong; Zhu, Xuemei; Deng, Xun; Yin, Hong; Jiang, Yanrong; Zhao, Mingwei; Li, Xiaoxin; Liang, Jianhong (Frontiers in Medicine, 2022)
Purpose: To compare the efficacies and treatment outcomes of intravitreal anti-VEGF agents and laser therapy in retinopathy of prematurity (ROP). Methods: A retrospective, nonrandomized, comparative study of patients diagnosed with type 1 ROP or aggressive posterior ROP (APROP) treated with intravitreal anti-VEGF agents or laser therapy as primary treatment at the People’s Hospital of Peking University. Results: A total of 1627 eyes of 862 patients were included. In Group 1, 399 eyes of 204 patients were diagnosed with APROP or zone I ROP. The initial regression of the anti-VEGF subgroup was better than that of the laser subgroup, and the reactivation rate and rate of progression to retinal detachment were lower than those of the laser subgroup. In Group 2, 1228 eyes of 658 patients were diagnosed with zone II ROP. The reactivation rate of the laser subgroup was lower than that of the anti-VEGF subgroup. No significant differences were found in the initial regression and the probability of developing retinal detachment. Among the anti-VEGF agents, the recurrence rate in eyes treated with conbercept was much lower than that in eyes treated with ranibizumab. The spherical power and spherical equivalents of eyes treated with laser were significantly higher than those of eyes treated with anti-VEGF agents 1 year after initial treatment. Conclusions: In contrast to laser therapy, anti-VEGF agents as primary treatments have potential advantages for eyes with zone I ROP and A-ROP. For eyes with zone II ROP, laser photocoagulation and anti-VEGF agents therapy showed similar efficacy; however, the rate of reactivation with laser therapy was significantly lower than that with anti-VEGF agents. Among the anti-VEGF agents, the recurrence rate was much lower in eyes treated with conbercept than in eyes treated with ranibizumab. Compared to anti-VEGF agents, laser treated eyes had greater trend to myopia.